Re‐defining ERM function in lymphocyte activation and migration. Issue 1 (10th October 2013) - Parameswaran, Neetha; Gupta, Neetu
Summary: Lymphocyte activation and migration involve large‐scale actin cytoskeletal remodeling. The Ezrin–Radixin–Moesin (ERM) family proteins reversibly link the plasma membrane and cortical actin meshwork and mediate the dynamic nature of the membrane‐cytoskeletal interface to facilitate remodeling. The reversibility of this linkage is controlled by the conformation of ERM proteins and depends on the phosphorylation of a conserved threonine residue in the actin‐binding domain. Disruption of the phospho‐cycling nature of ERM proteins through dominant negative and constitutively active mutants results in impaired lymphocyte migration and activation. In recent years, a novel role has emerged for ERM proteins as signaling scaffolds that can modulate B and T‐cell activation through additional posttranslational modifications at tyrosine residues. Here, we highlight recent studies that have redefined the role of ERM proteins in lymphocyte activation and migration. We discuss how lymphocyte‐specific knockouts of ERM proteins and high resolution imaging techniques have identified a novel function for them as rheostats that modulate the strength of antigen receptor signaling in B cells. Finally, we describe scenarios in which ERM protein function is coopted by pathogens for their own transmission and speculate on the potential of ERM proteins for regulating undesirable lymphocyte behaviors such as autoimmunity and malignancy.